41 Patterns of prior hospitalisation and arrest: a comparison of legal intervention firearm injuries to assault-related firearm injuries and motor vehicle injuries in seattle. (19th September 2017) - Mills, Brianna; Nurius, Paula; Matsueda, Ross; Rivara, Fred; Rowhani-Rahbar, Ali
Abstract : Statement of purpose: Legal intervention (LI) firearm injuries may occur after contact with both the legal and medical systems; examining arrest and medical records jointly may provide clearer information on risk markers for such injuries. We examined whether LI shooting victims differed from other firearm and non-firearm injury victims in their prior contacts with the legal and medical systems. Methods: We probabilistically linked 2010–2014 fatal and non-fatal LI and assault-related firearm injuries and unintentional motor vehicle crash (MVC) passenger injuries that either occurred in Seattle or were sustained by Seattle residents to statewide hospitalisation and arrest records. Multinomial logistic regression was used to compare the odds of arrest and hospitalisation for substance abuse or mental illness in the 2 years prior to injury among LI and assault-related firearm injury cases relative to MVC passenger injury controls, adjusting for age, race, and gender. Results: We identified 31 LI and 442 assault-related firearm injuries, and 331 MVC passenger injuries. LI and assault-related cases were more likely than MVC controls to have a felony record (OR=6.34; 95% CI: 2.29–17.53 and OR=4.26; 95% CI: 2.39–7.59, respectively). LI cases were more likely than MVC controls to have a conduct-related (OR=22.01; 95% CI: 1.44–335.93) or psychosis diagnosis (OR=5.37; 95% CI: 1.12–25.83). LI cases were more likely than assault-related cases to have a substance abuse (OR=3.91; 95% CI: 1.14–13.47) or mental illness hospitalisation (OR=3.44; 95% CI: 1.02–11.54). Conclusion: The burden of past arrest and substance abuse and mental illness hospitalisation was greater among LI firearm injury victims than among individuals with firearm assault or MVC passenger injuries. Significance: Joint review of arrest and medical records can differentiate LI firearm injury victims from victims with other injuries. Legal intervention firearm injury prevention strategies can be tailored using these patterns.